CONTRASTIVE ANALYSIS OF THE CONCEPT “FATHER” IN ENGLISH AND UZBEK LANGUAGES - Khayitova Shokhida Erkin Kizi (Western European Studies, 2024)
This article explores the concept of “father” in both English and Uzbek languages, focusing on how it is represented through linguistic expressions, idioms, and cultural values. By examining the concept of father in both languages, the study reveals the cultural nuances and differences that shape its meaning. In English, the father is often portrayed as a figure of guidance, wisdom, and individual empowerment, reflecting the individualistic nature of English-speaking cultures. Phrases like “father figure” and “father knows best” highlight the father's role in fostering independence and providing mentorship. In contrast, Uzbek expressions such as “Ota suyagi” and “Otaning duosi qanot” emphasize the father’s central role in family unity, collective identity, and the preservation of cultural traditions. The analysis underscores how language reflects cultural priorities, with the father representing both a moral guide and a symbol of family stability. By comparing these cultural perceptions of fatherhood, this study enhances our understanding of how deeply cultural values influence language and communication. The findings contribute to the field of cross-cultural communication, offering insights into the role of familial figures in different societies
Keywords: Father; Concept of father; English language; Uzbek language